PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI PADA PEMBELAJARAN DI MASA PANDEMI COVID 19 - Syarif Nugroho (JURNAL VOKASI DEWANTARA (JVD), 2023)
This study was conducted to describe the use of learning media technology during the corona virus pandemic. This kind of exploration is a quantitative descriptive research. Procedures for collecting information using questionnaires and documentation. The instrument in this examination uses a questionnaire. Side effects of the validity test using the used test. The consequence of the reliability test is that the value of Alpha = 0.880 is called high. The information investigation procedure uses a measurable examination of interest. The results showed that the use of learning media innovations during the COVID-19 pandemic was moderate. This classification is reinforced by the side effects of investigations on each marker. (1) The learning process using information and communication technology is an average of 13.24 classified as moderate; (2) The supporting and inhibiting factors for the application of the average of 12.51 are classified as moderate; (3) The effectiveness of the use of information and communication technology on average is 13.57 which is classified as moderate; (4) The results of the application of the use of information and communication technology in the average of 12.67 are classified as moderate.